2012
DOI: 10.1080/08974454.2012.716694
|View full text |Cite
|
Sign up to set email alerts
|

Significant Gender Differences in Factors Related to the Detention of Youthful Offenders

Abstract: An important priority of the U.S. juvenile justice system is to reduce the number of youthful offenders who are placed into secure detention placement. Though significant research examining these predictors exists, there is limited analysis of gender-specific predictors. Using existing juvenile court and mental health assessment case records of 433 youthful offenders from two Midwestern U.S. counties, this study sought to identify separately for males and females the legal (including number of delinquency adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous research has produced mixed results regarding gender differences in risk factors for delinquency. Some studies found gender differences (e.g., Mallett et al, 2012;Wiesner, 2003), whereas other studies did not find gender differences (e.g., Hodgins & Janson, 2002;Johansson & Kempf-Leonard, 2009;Sullivan, Veysey, & Dorangrichia, 2003). Given that only few studies examined the association between mental disorders and recidivism separately for males and females, future research should examine this issue in order to draw empirically well-supported conclusions.…”
Section: Moderator Effectsmentioning
confidence: 96%
“…Previous research has produced mixed results regarding gender differences in risk factors for delinquency. Some studies found gender differences (e.g., Mallett et al, 2012;Wiesner, 2003), whereas other studies did not find gender differences (e.g., Hodgins & Janson, 2002;Johansson & Kempf-Leonard, 2009;Sullivan, Veysey, & Dorangrichia, 2003). Given that only few studies examined the association between mental disorders and recidivism separately for males and females, future research should examine this issue in order to draw empirically well-supported conclusions.…”
Section: Moderator Effectsmentioning
confidence: 96%